2018
DOI: 10.1002/mus.26111
|View full text |Cite
|
Sign up to set email alerts
|

Predicting myofiber size with electrical impedance myography: A study in immature mice

Abstract: By using well-established statistical models, EIM data alone can provide a satisfactory estimate of myofiber size. Additional study of this approach for approximating myofiber size without the requirement of removing tissue for histological analysis is warranted. Muscle Nerve, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 16 publications
6
36
0
Order By: Relevance
“…In this study we have confirmed the ability of EIM to detect alterations in myofiber CSA, with the PolG animals most notably showing differences in the f c parameter, a value closely related to cell size . Previous studies, not using EIM, pooled male and female PolG mice to increase the statistical power based on a previous report indicating that there were no sex differences in mitochondrial oxygen consumption in the heart, skeletal muscle and liver, adenosine triphosphate content, mitochondrial H 2 O 2 generation, oxidative stress, and markers of apoptosis in WT mice of the same background .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study we have confirmed the ability of EIM to detect alterations in myofiber CSA, with the PolG animals most notably showing differences in the f c parameter, a value closely related to cell size . Previous studies, not using EIM, pooled male and female PolG mice to increase the statistical power based on a previous report indicating that there were no sex differences in mitochondrial oxygen consumption in the heart, skeletal muscle and liver, adenosine triphosphate content, mitochondrial H 2 O 2 generation, oxidative stress, and markers of apoptosis in WT mice of the same background .…”
Section: Discussionsupporting
confidence: 78%
“…In this study we have confirmed the ability of EIM to detect alterations in myofiber CSA, with the PolG animals most notably showing differences in the f c parameter, a value closely related to cell size. 24,25 Previous studies, 11,26 not using EIM, pooled male and female PolG mice to increase the statistical power based on a previous report indicating that there were no sex differences in mitochondrial oxygen consumption in the heart, skeletal muscle and liver, adenosine triphosphate content, mitochondrial H 2 O 2 generation, oxidative stress, and markers of apoptosis in WT mice of the same background. 27 However, here we found statistically significant differences in both con- In agreement with a previous study that evaluated EIM in a group of live 3-month-old and 25-month-old C57/B6 mice and showed an increase in both longitudinal and transverse f c in the aged mice, 8 in the present study we found a consistent increase in f c value in the untreated PolG mice, which correlates with the typical premature aging features associated with this model.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to our previous study that adopted an EIM‐based predictive approach, there were several major differences here. First, in the previous study, we used needle electrodes placed in only 1 direction (longitudinally).…”
Section: Discussionmentioning
confidence: 87%
“…We followed an approach analogous to that previously used . Briefly, we first standardized the mean muscle fiber size and the impedance parameters to unit normal scale to remove the effect of the underlying unit of measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation